Spatial and Temporal Selectivity of Translational Glass Patterns Assessed With the Tilt After-Effect. (May 2021) - Pavan, Andrea; Contillo, Adriano; Ghin, Filippo; Donato, Rita; Foxwell, Matthew J.; Atkins, Daniel W.; Mather, George; Campana, Gianluca
Glass patterns (GPs) have been widely employed to investigate the mechanisms underlying processing of global form from locally oriented cues. The current study aimed to psychophysically investigate the level at which global orientation is extracted from translational GPs using the tilt after-effect (TAE) and manipulating the spatiotemporal properties of the adapting pattern. We adapted participants to translational GPs and tested with sinewave gratings. In Experiment 1, we investigated whether orientation-selective units are sensitive to the temporal frequency of the adapting GP. We used static and dynamic translational GPs, with dynamic GPs refreshed at different temporal frequencies. In Experiment 2, we investigated the spatial frequency selectivity of orientation-selective units by manipulating the spatial frequency content of the adapting GPs. The results showed that the TAE peaked at a temporal frequency of ∼30 Hz, suggesting that orientation-selective units responding to translational GPs are sensitive to high temporal frequencies. In addition, TAE from translational GPs peaked at lower spatial frequencies than the dipoles' spatial constant. These effects are consistent with form-motion integration at low and intermediate levels of visual processing.